preschool children, coping mecanism, coloring play activities, hospitalization - Astarani, Kili; Sukoati, Suci (Jurnal Penelitian STIKES Kediri, 2012)
Children will experience the stress of hospitalization time due to changes in the environment. The purpose of this research was to analyze the influence of coloring activities toward the using of coping mecanism when hospitalization. Design of this research is pra eksperimental pre-post test one group design. This population is children preschool old even hospitalization at Kediri Baptist Hospital total sample was 31 respondent, sample taken on accidental sampling. Variable of this research were coloring play activities and coping mecanism. The data were collected by using questionaire. Collecting data using a statistical test by using wilcoxon signed range test with α≤0,05. The results showed that 24 respondent  change coping mecanism to positive range, 6 respondent  fixed on their coping mecanism before interview, and 1 respondent  change their coping mecanism to negative range. p=0,000. Concluded that coloring activities giving patients preschoolers will enhance adoptive coping mechanism when hospitalization.